Hydrodeoxygenation of furfuryl alcohol over Cu/MgAl and Cu/ZnAl catalysts derived from hydrotalcite-like precursors (2017)
The aqueous phase hydrodeoxygenation (HDO) of furfuryl alcohol over Cu/MgAl and Cu/ZnAl catalysts with different Mg/Al and Zn/Al molar ratios, were investigated. Mg-Al and Zn-Al mixed oxides derived from hydrotalcites precursors were used as supports, which were impregnated with an aqueous solution of copper nitrate by incipient wetness impregnation. The HDO reaction was carried out in a typical batch reactor at 5 MPa of H2 and 200 °C for 4 h. Among the catalysts studied, the Cu/MgAl-0.5 catalyst exhibited the higher furfuryl alcohol conversion (86%) and yield of cyclopentanol (35%), which is the reaction product with the highest hydrogen-carbon (H/C) ratio. With the Cu/MgAl-3 catalyst a high cyclopentanone yield (67%) was achieved. The results obtained, showed that copper supported on mixed oxides catalysts derived from hydrotalcite precursors are a promising alternative to improve the bio-oil quality.